Comparison of the BACTEC MYCO/F Lytic Bottle to the Isolator Tube, BACTEC Plus Aerobic F/Bottle, and BACTEC Anaerobic Lytic/10 Bottle and Comparison of the BACTEC Plus Aerobic F/Bottle to the Isolator Tube for Recovery of Bacteria, Mycobacteria, and Fungi from Blood - Vetter, E. (American Society for Microbiology, 2001)
The BACTEC MYCO/F Lytic blood culture bottle (Becton Dickinson Diagnostic Instrument Systems, Sparks, Md.) is designed to optimize the recovery of fungi and mycobacteria; however, this bottle also supports the growth of most aerobic bacteria. We compared the MYCO/F Lytic bottle with two other BACTEC bottles and the Isolator system for the recovery of bacteria as well as fungi and mycobacteria from blood. A total of 6,108 blood culture sets were inoculated with blood obtained from adult patients. Twenty-five to 28 ml of blood collected by a phlebotomy team for each blood culture set was randomly distributed into each of four blood culture receptacles: the Isolator tube (Wampole Laboratories, Cranbury, N.J.) and three BACTEC bottles: the MYCO/F Lytic bottle, the BACTEC Plus Aerobic/F bottle, and the BACTEC Anaerobic Lytic/10 bottle. The sediment from the Isolator tube was inoculated onto chocolate agar (CA), brain heart infusion agar (BHI), and Sabouraud dextrose agar (SDA) and into a BACTEC 13A bottle. Incubation durations were as follows: MYCO/F Lytic bottle, 42 days; Plus Aerobic/F bottle, 5 days; Anaerobic Lytic/10 bottle, 5 days; sediment from Isolator tube on CA, 3 days; sediment from Isolator tube on BHI, 30 days; sediment from Isolator tube on SDA, 30 days; and sediment from Isolator tube in a BACTEC 13A bottle, 42 days. Two isolates of Histoplasma capsulatum were recovered from the Isolator tube only. Three isolates of Mycobacterium tuberculosis complex were recovered: two isolates from the MYCO/F Lytic bottle only and one isolate from the Isolator tube (whose sediment was inoculated into the BACTEC 13A bottle) only. Two isolates of Cryptococcus neoformans were recovered: one from the MYCO/F Lytic bottle only and the other from the MYCO/F Lytic bottle and the Isolator tube (whose sediment was inoculated into the BACTEC 13A bottle). For potential pathogens overall, there was a statistical difference in recovery that favored the Isolator system over the MYCO/F Lytic bottle (P = 0.0015), including statistically significant differences for Staphylococcus aureus (P = 0.0001) and Streptococcus pneumoniae (P = 0.0313). However, there was no statistically significant difference between the two blood culture systems when detection of bloodstream infection was considered. The time to detection for all potential pathogens combined was less for the MYCO/F Lytic bottle than for the Isolator system (P = 0.0004). Overall, the potential pathogen recovery was greater for the BACTEC Plus Aerobic/F bottle than for either the Isolator system (P = 0.0003) or the MYCO/F Lytic bottle (P = 0.0001). However, the BACTEC Plus Aerobic/F bottle did not recover M. tuberculosis, H. capsulatum, or C. neoformans isolates. The combination of the Isolator system and MYCO/F Lytic bottle may be useful as a selective blood culture method to optimize the recovery of fungi and mycobacteria from blood. Compared with the manual Isolator system, the MYCO/F Lytic system has the advantage of less preanalytic processing and continuous automated monitoring of bottles for growth by the BACTEC 9240 instrument.